Surgical treatment for bleeding ileal varices: A case report. (November 2021) - Haddad, Anis; Beji, Hazem; Chaker, Youssef; Maghrebi, Houcine; Jouini, Mohamed; Kacem, Montassar
Abstract: Introduction and importance: Bleeding from ileal varices is a rare and a life-threatening situation. Its management is difficult and includes endoscopic, surgical and interventional radiology treatment. Here we report a successful emergency surgery for bleeding ileal varices in a patient with cirrhosis due to autoimmune hepatitis. Presentation of a case: A 60-year-old woman was admitted for rectal bleeding. She had a history of autoimmune hepatitis. She was treated by endoscopic ligation for oesophageal varices. Eso-gastro-duodenal fibroscopy and colonoscopy failed to reveal the bleeding site. CT scan was then performed showing ileal varices due to a portocaval shunt, there was a communication between the superior mesenteric vein and the right internal iliac vein. As the embolization was not feasible and the bleeding did not stop, an exploratory laparotomy was performed showing two dilated veins on the surface of the ileal wall, communicating with the right internal iliac vein. We performed a ligation of the vessels. Postoperative course was uneventful. Discussion: Ectopic varices are a rare case of gastrointestinal bleeding. Most of those patients have portal hypertension and liver cirrhosis. Diagnosing bleeding ileal varices is difficult because endoscopic examination can't always reveal the bleeding site. Interventional radiology is a good option for patients having bleeding ileal varices knowing that they often have advanced liver cirrhosis making them poor candidates for surgery. Haemostasis by endoscopy is often temporary and bleeding frequently recurs. Surgery should be considered if non-invasive treatments failed to ensure the haemostasis. Conclusion: Bleeding ileal varices is a rare situation. Interventional radiology and endoscopy can be good options. If not feasible, surgical treatment should not be delayed. Highlights: Ectopic varices are a rare case of gastrointestinal bleeding. Diagnosing bleeding ileal varices is difficult. Surgical treatment is the best option to stop the bleeding.